PENGARUH PROFITABILITAS DAN KEBIJAKAN HUTANG TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013 SAMPAI DENGAN 2017 - Mulyana Sari; Makhdalena Makhdalena; Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This Study aims to determine the influence of profitability and debt policy on dividend policy both of simultaneously and partialy at manufacturing companies of food and baverages sub sector which is listing in the Indonesia Stock Exchange period 2013 until 2017. The population of this study is all of the companies of food and baverages sector which is listing in the Indonesia Stock Exchange period 2013 until 2017 which data was examined by census. This study used secondary data sourced from company’s annual report. The data analysis technique used path analysis with the help of the program called SPSS (Statistical Package for Social Science). The result of this study showed that profitability and debt policy simultaneously had an influence on dividend policy. Profitability partially had a positive influence on dividend policy. While debt policy had a negative influence on dividend policy.Key Words: Profitability (ROA), Debt Policy (DER),, and Dividend Policy (DPR)